Dwa inwentarze zamku w Besiekierach - Kajzer, Leszek (Acta Universitatis Lodziensis. Folia Archaeologica, 1983)
In this article there are contained two inventories of the castle at Besiekiery near Łódź coming from 1704 and 1715. Their manuscripts are kept in the Chief Registry of Old Acts in Warsaw within a complex of relations of Juridicial Books from Łęczyca (Castrensia Lanciciensia relationes). The Blesiekiery Castle was an object of numerous field and interior surveys (see biographical notes 1—5 in this article). Both inventories included here aloing with a younger one coming from 1733 and published by the author in 1980 (see biographical note No. 5) provide a good basis for further studies on the castle's history. They describe the state of the object at the beginning of 18th century w h en following the Baroque remodelling of the castle by the starost of the district — Jan Szymon Szczawiński done in mid — 17th century a gradual decline of the castle began. Consecutive descriptions miss details of interior decoration and arms stored in the castle with a decreasing number of chambers being suitable for l iv in g purposes. In the second half of 18th century there was pulled down the second floor of „the big manor" and the final ruination of the castle began. Its largely depleted relicts have been preserved till today and they should become an object of the conservator’s work,